A prospective study of surgical management of Koch’s abdomen in a tertiary care hospital - Shukla, Archana; Kori, Rajpal; Shivhare, Rahul; Dhurve, Lalit; Gautam, Sonveer (International Surgery Journal, 2021)
Background: Tuberculosis is a communicable disease that is a major cause of morbidity and mortality worldwide. Abdominal tuberculosis is the sixth most common form and is associated with serious complications like perforation and stricture formation. Methods: Observational and prospective study conducted in Hamidia Hospital, Bhopal from September 2018 to September 2020 included 122 patients, between the age of 16 to 60 years who underwent surgical management of abdominal tuberculosis. Results: The incidence of abdominal tuberculosis was higher in young age groups mostly belonging to male sex. The most common presentation was of subacute intestinal obstruction. On surgical exploration ileocecal tuberculosis was the most common finding which was managed most commonly by segmental resection with anastomosis followed by adhesiolysis and strictureplasty. Post-operative wound infection was the most common complication followed by pulmonary complication which was the most common cause of death. Conclusions: Early diagnosis of abdominal tuberculosis with the help of newer diagnostic tools and early referral to higher centers is necessary to decrease the morbidity and mortality. Early start of anti-tubercular drug therapy along with surgical management can help us reduce the mortality and long-term complications associated with abdominal tuberculosis.